Desnaturalización de la acción de protección como mecanismo para evadir decisiones judiciales en Ecuador. - Arcos León, Edison Jair (2025)
This Curricular Integration Project analyzes the denaturalization of the protection action in the Ecuadorian judicial system, focusing on its misuse to evade judicial decisions. The problem lies in the actions of judges and lawyers who distort this jurisdictional guarantee, driven by factors such as corruption, lack of specialized judges and ignorance of the constitutional norm. The need for a correct application of the action of protection and its implications on legal security, due process and the denaturalization of constitutional justice are highlighted. The methodology used was with an analytical approach, through surveys to 30 legal professionals and interviews to 5 experts in the field. Techniques such as online surveys and face-to-face interviews were used. The results showed that the inadequate use of the action for protection and other jurisdictional guarantees seriously affects the principles of due process and generates concerns in the administration of justice. As recommendations, it is proposed that the Judiciary Council train judges, prosecutors and lawyers on the scope and limits of the action for protection, as well as the consequences of its abuse. It also emphasizes the need to implement specialized courts in constitutional matters and that the Constitutional Court establish more rigorous criteria for the selection of constitutional judges, prioritizing their experience in human rights and legal training in constitutional justice. In conclusion, the research highlights the urgency of adequately regulating the action for protection to avoid denaturalization as a tool to circumvent judicial decisions, proposing guidelines for its optimization and strengthening confidence in the justice system.